Strictly for laughs - Conford, Ellen (New York : Pacer Books, 1985)
An aspiring disc jockey and an aspiring comedian find their comfortable relationship becomes quite stormy when they get their big change to pursue their dreams.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
6.0
6.0
7-10.
Keywords: Comedians -- Fiction; Radio broadcasting -- Fiction; Comedians -- Fiction; Radio broadcasting -- Fiction